2022
DOI: 10.3389/fnut.2022.1033375
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dyslipidemia on the severity of symptomatic lumbar spine degeneration: A retrospective clinical study

Abstract: BackgroundLumbar intervertebral disc degeneration (IVDD) is an important cause of low back pain or sciatica, and metabolic factors play an important role. However, little is known about the relationship of dyslipidemia to the risk of intervertebral disc degeneration (IVDD). This study aimed to assess the impact of serum lipid levels on the severity of lumbar disc degeneration and to investigate its association with endplate inflammation.MethodsWe conducted a case retrospective study in which a total of 302 hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…Based on the mechanism that CLBP can be caused by hypertension-induced aneurysms in the aorta adjacent to the lumbar region [ 7 ]. One study reported a positive relationship between hypertension and CLBP [ 11 ], another found a significant association between hypertension and severe CLBP [ 23 ], and an additional study reported a significantly increased risk of CLBP in a group of men with hypertension [ 13 ]. Based on the above, we assumed that there would be a positive relationship between hypertension and CLBP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the mechanism that CLBP can be caused by hypertension-induced aneurysms in the aorta adjacent to the lumbar region [ 7 ]. One study reported a positive relationship between hypertension and CLBP [ 11 ], another found a significant association between hypertension and severe CLBP [ 23 ], and an additional study reported a significantly increased risk of CLBP in a group of men with hypertension [ 13 ]. Based on the above, we assumed that there would be a positive relationship between hypertension and CLBP.…”
Section: Discussionmentioning
confidence: 99%
“…Yuan et al found that Chinese individuals with high TG ≥ 6.2 mg/dL (OR, 1.775; 95% CI, 1.209, 2.606) and high LDL ≥ 4.1 mmol/L (OR, 1.818; 95% CI, 1.123, 2.943) tended to have a higher risk of developing lumbar intervertebral disc degeneration, a known cause of LBP [ 22 ]. Similarly, a retrospective study of 320 Chinese patients and a case-control study of 105 Koreans by Haung et al found that higher total cholesterol and TG levels were associated with increased lumbar intervertebral disc degeneration and a significantly higher incidence of LBP [ 23 , 24 ]. A case-control study of 269 patients found an increased risk of intervertebral disc degeneration in the setting of dyslipidemia with high TG (OR, 1.753; 95% CI, 1.151, 2.699; p = 0.009), high LDL (OR, 1.952; 95% CI, 1.530, 2.490; p < 0.001), or high total cholesterol (OR, 3.580; 95% CI, 2.182, 55.876; p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the results of our study, most studies have suggested that HDL is closely related to IVDD. A retrospective clinical study involving 302 patients found that the top two factors affecting the severity classi cation of IVDD were age (32.9%) and HDL (20.7%), and suggested that increased HDL levels may reduce the incidence of IVDD (5) . A similar conclusion was reached by another retrospective study including 790 patients, who found that the ratio of TC/HDL-C and LDL-C/HDL-C were signi cantly associated with lumbar disc herniation (LDH) (36).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that lipid metabolism is closely related to IVDD (4). A retrospective case study including 302 patients showed that high-density lipoprotein (HDL) and triglyceride (TG) are important factors affecting the degree of intervertebral disc degeneration (5). An observational study found that high LDL levels was strongly associated with L4/5 disc degeneration (OR, 2.65) (6).…”
Section: Introductionmentioning
confidence: 99%